Highly selective tungstate transporter protein TupA from Desulfovibrio alaskensis G20 - Otrelo Cardoso, Ana Rita (2017)
Molybdenum and tungsten are taken up by bacteria and archaea as their soluble oxyanions through high affinity transport systems belonging to the ATP-binding cassette (ABC) transporters. The component A (ModA/TupA) of these transporters is the first selection gate from which the cell differentiates between MoO4 2-, WO4 2- and other similar oxyanions. We report the biochemical characterization and the crystal structure of the apo-TupA from Desulfovibrio desulfuricans G20, at 1.4 Å resolution. Small Angle X-ray Scattering data suggests that the protein adopts a closed and more stable conformation upon ion binding. The role of the arginine 118 in the selectivity of the oxyanion was also investigated and three mutants were constructed: R118K, R118E and R118Q. Isothermal titration calorimetry clearly shows the relevance of this residue for metal discrimination and oxyanion binding. In this sense, the three variants lost the ability to coordinate molybdate and the R118K mutant keeps an extremely high affinity for tungstate. These results contribute to an understanding of the metal-protein interaction, making it a suitable candidate for a recognition element of a biosensor for tungsten detection.